Combatting fraud as a disincentive of an unintended economic migrant: A comparative review of the direct Turkish model and the indirect Australian model - Ozyurek, Sherene; Fernandez, Rodger (Border Crossing, 2016)
Under the new Turkish Law on Foreigners and International Protection (Article 54) represents a rapid deterrent approach as the consequences of fraud are implemented within 30 days. In contrast to the Turkish approach, Public Interest Criteria 4020 used in Australian law implies a lengthy process that may take up to two years. A quantitative analysis of retrospective data (2010-2014) of the Australian Migration Review Tribunal substantiated the notion that in contrast to the Turkish model, the Australian model is used as a procrastinating tool to the advantage of unintended economic migrants to remain in Australia.